Pengalaman Penyalahguna Narkoba Dengan Program Intervensi Berbasis Masyarakat (IBM): Studi Fenomenologi Pada Mantan Klien Rehabilitasi - Putri Hapsari Ramadhani; Chr. Argo Widiharto; Venty Venty; Sardiyanto; Aloysius Ayusta Thobie (Institut Agama Islam Negeri Curup, 2026)
This study explores the subjective experiences of former rehabilitation clients after participating in a Community-Based Intervention (IBM) program. Using a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA), this study involved two former rehabilitation clients who had completed the IBM program for at least six months. Data were collected through in-depth semi-structured interviews. IPA analysis was used to interpret participants’ lived experiences, while NVivo 12 Plus assisted in organizing and coding the data. The findings revealed that participants experienced emotional recovery, increased self-confidence, improved health awareness, and significant changes in life perspectives after rehabilitation. Recovery was interpreted not merely as abstinence from drug use, but as a process of rebuilding self-identity, restoring meaning in life, and developing confidence to maintain positive behavioral changes. However, participants continued to face challenges such as social stigma and pressure from former peer environments. The study concludes that IBM plays an important role in psychosocial recovery through social support, community mentoring, and the strengthening of self-efficacy among former clients.